L'Islam spiegato ai miei studenti: Otto lezioni su Islam e diritto - Fiorita, Nicola (Studi e saggi, 2006)
The rooting of the Italian Muslim presence raises, beyond any exploitation, problems of a different nature that are difficult to solve. Inevitably, the need to understand the content of the principles and rules that govern Islam is destined to grow and pass from the restricted circle of specialists to the wider audience of legal, social and cultural operators. This agile volume, created to provide students with easy-to-use teaching material, tries to intercept this question through seven lessons that summarise the peculiar profiles and the most current issues of the Islamic legal system such as sources, marriage, the theme of human rights, female genital mutilation and the birth of Islamic banks. In the final part of the volume, ample space is given to the solutions that Western legislators have (or have not) developed to respond to the specific needs of Muslims living in Europe